2017
DOI: 10.1097/prs.0000000000003082
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer Effects of Artificial Red Cells on Dye Laser Irradiation in an Animal Model Assuming Port-Wine Stain Treatment

Abstract: Hemoglobin vesicles can function as photosensitizers to destroy the vessel wall. A possible mechanism of pulsed dye laser-resistant port-wine stains is that overly small vessels do not contain sufficient red blood cells. They are therefore poor absorbers/heaters for these lasers. Hemoglobin vesicle combination therapy will improve clinical outcomes of dye laser treatment against such lesions only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Rikihisa et al reported utilization of HbV as a photosensitizer, a target of laser treatment of port-wine stain (capillary malformation) [44], because injection of HbV can increase capillary Hb levels effectively as depicted in Figure 3B, producing more heat and photocoagulation.…”
Section: Potential Usage Of Hbv As An Oxygen Carrier For Ischemic mentioning
confidence: 99%
“…Rikihisa et al reported utilization of HbV as a photosensitizer, a target of laser treatment of port-wine stain (capillary malformation) [44], because injection of HbV can increase capillary Hb levels effectively as depicted in Figure 3B, producing more heat and photocoagulation.…”
Section: Potential Usage Of Hbv As An Oxygen Carrier For Ischemic mentioning
confidence: 99%
“…Following the injection of Hb-Vs (at a dose of one-tenth of the circulating blood volume), the microvessels were observed to expand and to become markedly dense. The specific area of the microvessels in a bird’s-eye view increased by 20% after the injection (Figure 4) [1]. …”
Section: Break Through the Limits Of Laser Treatment Against Pws Wmentioning
confidence: 99%
“…Absorbance at 595 nm at various concentrations of Hb was determined using a spectrophotometer. The hBlood, Hb-V and Mixed group samples all showed the same absorbance at 595 nm at all concentrations of Hb (Figure 6) [1]. …”
Section: Break Through the Limits Of Laser Treatment Against Pws Wmentioning
confidence: 99%
See 2 more Smart Citations